PENGARUH PENERAPAN METODE INDEX CARD MATCH (ICM) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN PEKAN SELASA KABUPATEN SOLOK SELATAN - Amrayeti, Dona; Rahmi, Rahmi; Fitri, Dewi Yuliana (Pendidikan Matematika, 2013)
The research is motivated by the lack of class VIII student learning outcomes MTsN Pekan Selasa Kabupaten Solok Selatan. Research is caused by the applied mathematic instructional strategies teacher are less variable, the learning process is centered on the teacher so that, the learning occurs is one-way. One method to overcome these problems by applying the method of Index Card Match (ICM) in learning. This study aims to determine whether students understanding of mathematical concepts by applying method of Index Card Match (ICM) is better than student understanding of mathematical concepts with conventional teaching eighth grade students MTsN Pekan Selasa Kabupaten Solok Selatan. The type of research is the design of experimental studies Against Random Subjects. The research instrument is the final test in the form of essays. The Â hypothesis testing using t-test of the parties with the help of MINITAB, obtained P-value of 0.000 is smaller than a = 0.05, so it can be concluded that the students understanding of mathematical concepts by applying method of Index Card Match (ICM) is better than understanding concepts conventional mathematical learning.